To be Buried Inside a Long-Forgotten World: Studying the Reuse of Passage Graves Wearing “Bronze Age Glasses” - Gustav Wollentz (Current Swedish Archaeology, 2012)
The theories presented about the reuse of Neolithic monuments during the Bronze Age in Scandinavia are mainly universal, i.e. applicable to all periods during prehistory. I argue that there is no point in isolating reuse as something separate from society. The focus of my study is the Mysinge passage grave on the is- land of Öland. I have also studied the reuse of other graves on Öland and of passage graves in Falbygden. I propose that the passage grave was linked to the un- derworld and that some of those buried in the cham- ber of Mysinge during the Bronze Age were people travelling by sea.